Moderating Effects of Personality Traits On Online Learning Transition and Acceptance Among Culinary Arts Students - Hashim, Noliza; Mohamed, Misrah Hamisah; Aziz, Liara Azniza; Abd Patah, Mohd Onn Rashdi (Journal of Technical Education and Training, 2022)
Many Higher Education Institution (HEI) students had to make an immediate change to online learning from the conventional face-to-face mode due to the COVID-19 pandemic and Movement Control Order (MCO) imposed by the government. Learning practical courses such as Culinary Arts via online without application or practical work generated bigger challenges for HEIs. It was emphasised that Culinary Arts education depends predominantly on hands-on application and training. The purpose of this study is to investigate Culinary Arts program students’ acceptance of online learning methods (hands-on learning at home) and how the Big Five Personality Traits (BFPT) could have an impact on the relationship. A total of 234 responses from Culinary Arts based program students of six (6) HEIs in Malaysia were obtained and analysed using SPSS statistical software. Findings showed that students were able to accept the transition in learning from face-to-face to online learning. However, it was found that BFPT did not have a significant moderating impact on the relationship between Learning Transition and Online Learning Acceptance. The results could help HEIs in adapting to the new Learning Transition without compromising the quality of the graduates and the curriculum set by the institutions. In addition, the results of this study could enhance further investigations on Online Learning Acceptance to a wider scope and type of study programs.